Fault nucleation, restriction, and aspect ratio in layered sections: Quantification of the strength and stiffness roles using numerical modeling. Issue 8 (14th August 2013) - Roche, V.; Homberg, C.; Rocher, M.
Abstract : [1] 3D numerical modeling has been used to investigate how the variations of mechanical properties in sedimentary layered sections affect the development of normal faults. We calculated the distribution of the Coulomb stress to assess the proximity of the layers to failure through an elastic layered section. The simulation of various combinations of rock properties allowed us to compare the effect of the stiffness and strength contrasts, which promote or inhibit faulting in the stiff layer, respectively. For rock systems showing little variation in strength, nucleation of the fault occurs in the stiff layer (e.g., limestones or sandstones), whereas it occurs in the compliant layer (e.g., clay‐rich rocks) if the stiff layer has a high cohesion. Considering a mean strength profile of the carbonate sequences, nucleation occurs in limestones if the ratio of Young's moduli between the limestone and clay‐rich rock is greater than 2; otherwise, clay‐rich layers fail first. We also showed that nucleation is promoted in sandstones or limestones if these layers are thinner than the clayey layers. In a second set of simulation, using a slip on a fault, we examined the conditions needed to overcome the restriction of the fault propagation. Our results suggest that the lateral propagation of the fault, within a layer, produces increasingly favorable conditions for vertical propagation. A maximum aspect ratio of width to height of 13 is predicted for faults in limestone‐clay sequences, and this maximum aspect ratio is expected to decrease as the contrast in the rock properties decreases. Key Points: 3D numerical modeling of fault growth mechanical properties in sedimentary layered sections assessment of the faulting